2012
DOI: 10.3109/00207454.2012.707713
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Qigong Exercise in Patients With Fibromyalgia: A Pilot Study

Abstract: Qigong exercise may potentially be an effective self-management approach in controlling FM symptoms. In this pilot study, regular daily Qigong exercise, accumulated number of exercise sessions, and the specific form of Qigong exercise may all be important factors for the significant improvement in the study subjects. Future research is required to determine whether the same benefit can be obtained in a larger sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 47 publications
1
42
1
Order By: Relevance
“…35 Qigong was also found to improve sleep in perimenopausal women 36 and women with fibromyalgia. 37,38,39 Similar to these studies, we also found a decrease in depressive symptoms and self-reported sleep duration (PSQI). Controlled breathing exercises also improved anxiety and depression in a sample of patients with chronic obstructive pulmonary disease.…”
Section: Discussionsupporting
confidence: 87%
“…35 Qigong was also found to improve sleep in perimenopausal women 36 and women with fibromyalgia. 37,38,39 Similar to these studies, we also found a decrease in depressive symptoms and self-reported sleep duration (PSQI). Controlled breathing exercises also improved anxiety and depression in a sample of patients with chronic obstructive pulmonary disease.…”
Section: Discussionsupporting
confidence: 87%
“…There are many unknown elements in this anecdotal study that need a more systematic study with a more sophisticated design. Although there are some reported positive outcomes in randomized control trials of Qigong therapy as a self-care method [20,21] rigorous trials are needed to examine the true effect of EQT on patients with FMS and other chronic pain syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial, long-term effect of the practice, consisting in the reduction of the stress and anxiety level, the normalization of blood pressure and the reduction of pain and muscular tension, have been clinically proven [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the expert knowledge literature does not contain information on the use of qigong in stuttering therapy, the long-term effect of the exercises, such as the reduction in the level of stress, anxiety and muscular tension, has been clinically confirmed [22,26].…”
Section: Discussionmentioning
confidence: 99%